Comparison of the effect of skin closure materials on skin closure during cesarean delivery. - Ye Huang; Xinbo Yin; Junni Wei; Suhong Li (PLoS ONE)
Objective To compare the effect of skin closure materials on skin closure during cesarean delivery. Methods We searched EMBASE、PubMed、Scopus、Cochrane CENTRAL for randomized controlled trials (RCTs) on the use of closure materials for skin closing effect during cesarean delivery. The outcomes were time to skin closure of dermal and epidermal layer, skin separation rate and wound complications(wound infection, hematoma,seroma, reclosure, readmission) reported as an odds ratio (OR) and surface under the cumulative ranking curve analysis (SUCRA) score. Results Twenty -six RCTs met the inclusion criteria. In the network meta-analysis (NMA) for time to skin closure of dermal and epidermal layer, pooled network OR values indicated that staple (network SMD, -337.50; 95% CrI: -416.99 to -263.18) was superior to absorbable suture. In the Skin separation NMA, pooled network OR values indicated that the absorbable suture (network OR, 0.37; 95% CrI: 0.19 to 0.70) were superior to staple. In the wound complications NMA, pooled network OR values indicated that the no interventions were superior to staple. Conclusion In conclusion, our network meta-analysis showed that the risk of skin separation with absorbable suture after cesarean delivery was reduced compared with staple, and does not increase the risk of wound complications, but the wound closure time would slightly prolonged.